Aires protégées et lutte contre les bioinvasions : des objectifs antagonistes ? Le cas de Psidium cattleianum Sabine (Myrtaceae) autour du parc national de Ranomafana à Madagascar. - Stéphanie M. Carrière; Eric Randrianasolo; Julie Hennenfent (VertigO)
Bioinvasion is a subject that has not been widely addressed and taken into account within environmental policy in Madagascar. However, many studies seem to show how ecosystems and species could be threatened in the medium term by invasive species. This study attempts to understand the history of introduction of Psidium cattleianum into the area of the Ranomafana-Andringitra corridor (between two ecologically-contrasting sites on the Malagasy highlands) and analyzes the ecological dynamics during the invasion of a site by this species and characterizes its effects on the biodiversity. Furthermore, the role of the faunal species as seed-dispersers (man, bovines and indigenous animals of the Ranomafana National Park) seems to be key vectors of the invasion. Finally, the important use of P. cattleianum by the local populations has been demonstrated in order to discuss a possible integrated effort to combat this highly invasive species while providing an economic return.